A newborn presenting with epidermolysis bullosa with duodenal atresia: A very rare case report and review of the literature - Sharad Bansal; Prem Prakash Gupta; Deepak Sharma; Shweta Bansal (Mashhad University of Medical Sciences, 2015)
Background: Epidermolysis bullosa (EB) comprises a group of genetically determined skin fragility disorders, which are characterized by blistering of the skin and mucosa, in response to little or no apparent trauma. These disorders represent heterogeneous phenotypes and are associated with various complications ranging from localized skin fragility to neonatal death. Nevertheless, the term "Epidermolysis" is a misnomer as epidermal disruption is not the principal alteration in two of the primary types of EB. In clinical, laboratory and epidemiological studies, this complex and heterogeneous group of disorders is classified, on the basis of the mode of inheritance, into three major types: EB simplex (EBS), junctional EB (JEB) and dystrophic EB (DEB). EB is a rare disease with an incidence rate of approximately 50 in 1 million live births, and 9 in 1 million people in the world population. Of these cases, about 92% are EBS, 5% are DEB, 1% is JEB and 2% are unclassified (1). Case presentation: In this study, we presented the case of a male newborn with EB and concomitant pyloric stenosis. To the best of our knowledge, only one case of this rare combination of EB with duodenal atresia has been retrieved in PubMed.